PENGARUH KUALITAS LAYANAN, PERSEPSI RISIKO, PERSEPSI KEPERCAYAAN TERHADAP PENGGUNAAN SISTEM PAJAK ELEKTRONIK DI KOTA BATAM - Maharani Anisya Putri; Sukartini Sukartini; Afridian Wirahadi Ahmad (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of service quality, risk perception, and trust perception on the use of electronic tax systems in Batam City. These factors were examined using a quantitative approach through a survey method involving 110 individual taxpayers (WPOP) selected through sampling techniques. Data were collected via questionnaires and analyzed using multiple linear regression analysis to identify the relationships between independent and dependent variables. The results indicate that service quality and trust perception have a positive and significant effect on the use of electronic tax systems, whereas risk perception has a significant effect. The findings imply that enhancing service quality and building taxpayer trust are crucial for increasing the adoption of electronic tax systems. This research also contributes theoretically to the application of the Theory of Planned Behavior (TPB) in the context of electronic taxation in Indonesia.